The Nature of the Logistic Function as a Nonlinear Discrete Dynamical System - Mensah, Patrick Akwasi Anamuah (2017)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Philosophy in Pure Mathematics,